Licensavtalet och konkurrensrätten - Gölstam, Carl Martin (Uppsala universitet, 2007)
The purpose of this thesis is to describe and analyse the significance of economic thinking and arguments in the treatment of licence agreements in EC competition law. A central question is to what degree the concept of competition in EC law reflects an economically realistic approach to competition. The study also investigates to what degree the economic functioning of intellectual property is considered in competition regulation and how much the economic functioning of the licence agreement is considered. The investigation mainly consists of a comparative analysis of EC competition law and American antitrust law concerning the economic arguments and their importance. The treatment of territorial restrictions, field of use restrictions, quantity clauses, tie-outs, tie-ins, grant back, no-challenge clauses and price restrictions are of special interest here. This study shows that an economically realistic view of competition has influenced current EC competition law, especially in the Technology Transfer Block Exemption Regulation (TTBER). Exceptions from this development in the EC law are mainly due to the goal of integration of the common market. Territorial restrictions are strictly regulated in the TTBER even when the parties’ market shares are below the market thresholds defined in the regulation. The function of intellectual property rights are not much considered in EC competition law but there are general remarks about the economic functioning of patents in the Guidelines for the TTBER. However, it is difficult to find evidence for economic reasoning about patents in the formation of concrete rules. On the contrary, patents are weakened by the widened concept of exhaustion presented in the Guidelines. The economic functioning of the licence agreement is considered in the rules of TTBER and the economic arguments for clauses which create incentives for making investments or give the possibility of control are acknowledged. However, the free riding argument has a weak position when applied to territorial restrictions, which are more formalistically regulated. The EC competition law has become more similar to American antitrust law. The decisive difference consists in the judicial treatment of territorial restrictions, where the goal of integration is still of central importance in EC law.
Skrifter från Juridiska fakulteten i Uppsala, ISSN 0282-2040 ; 110
Keywords: Antitrust Law; Civilrätt; Competencia; Competition law; Immaterialrätt; Intellectual property; Know-how; Konkurrensrätt; Law and Economics; Licence agreement; Licensavtal; Licensing; Patent; Private law; Rättsekonomi; Technology transfer; Tekniköverföring

Konkurrenslagen och konkurrensbegränsande offentliga regleringar - Edwardsson, Eva (Uppsala universitet, 2003)
The dissertation addresses the problem of how conflicts between the Swedish Competition Act (SFS 1993:20) and anti-competitive state regulations are to be solved. The study focuses on the legal situation in Sweden after 1993, when a new competition law was enacted and after the Swedish Membership of the European Union 1995. A comparative survey of how similar conflicts are solved in American Law, EU Law and Danish Law is made. The rationale behind the reform of the competition legislation in Sweden was the consideration that competition did not work well enough on Swedish markets. One important reason for this was thought to be the existence of regulations with a negative impact on competition. The solution of the problem was thought to reside in the adjustment of the Swedish competition legislation to the rules of the European Community (EC). After this substantial legal reform, a change in how anti-competitive regulations are dealt with could be expected. This study shows, however, that there has been practically no change at all. When conflicts between the Competition Act and anti-competitive regulations do occur, the Swedish Competition Authority evaluates the applicability of the regulation to see if a conflict really is at hand. In this legal process it is suggested that the regulation and not the Competition Act should be interpreted narrowly. This study shows that such a restrictive approach can be justified when taking the relevant sources of law into account. In cases where a disturbance to competition is the direct and necessary consequence of a clear regulation – with due considerations to EC Law – the regulation prevails. When these conditions are not at hand, it can be justified to give priority to the Competition Act.
URN: urn:nbn:se:uu:diva-3442 OAI: oai:DiVA.org:uu-3442 DiVA, id: diva2:162826
Keywords: Competencia; Competition law; Concurrence (droit); EG-rätt; EU-rätt; Europarätt; Konkurrensbegränsande; Konkurrenslagen; Konkurrensrätt; Regleringar